'SNOMEDizing' Questionnaires for Standardizing Stroke Registry Data - Riedel, Andrea; Schulz, Stefan; Martínez Costa, Catalina (Studies in Health Technology and Informatics, 2024)
International interoperability of healthcare and research data requires a commitment to standards. To this end, SNOMED CT was evaluated for representing questionnaire items of the European Registry of Stroke Care Quality using a complex annotation protocol. The agreement between validators and annotators was 72.4%. At least 64% of the information could be represented by using SNOMED CT only, including complex post-coordinations. 9% of the information would require an information model, and 14% the addition of new content to SNOMED CT. Next steps will be the creation of an annotation guideline for questionnaires, a specific reference set, and the combination of both with an information model such as HL7 FHIR.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Information model; Interoperability; SNOMED CT; Stroke